Optical Code Division Multiple Access for FTTH system - Bouregaa, Mouweffeq; Chikh-Bled, Mohammed El Kebir; Debbal, Mohammed; Ouadah, Mohammed Chamse Eddine; Chikh-Bled, Hicham (Photonics Letters of Poland, 2018)
Many multiple access techniques have been proposed and demonstrated to provide flexible solutions for FTTH network configurations. The performance of this system suffers because of the correlation properties that contribute to a high level of Multiple Access Interference (MAI), low system capacity (users), and lower transmission rate. In this paper, we have proposed Optical CDMA (OCDMA) as a configuration solution for FTTH networks to improve the performance of this type of network. Full Text: PDF References . Z. Mateusz, M. Mariusz, On cost of the uniformity in FTTH network design, Conference on Transparent Optical Networks (2017), 87-90 CrossRef CEDRIC F. LAM, Passive Optical Networks- Principles and Practice, first ed., British Library, USA, 2007. DirectLink M.K. Abdullah, W.T. P’ng, P.W. Lau, E.R. Tee, FTTH access network protection using a switch, Asia Pacific Conference on Communications (APCC), 3(2003) 1219–1222. CrossRef J. Ronnakorn, S. Napat, L. Somkiat, Design and implement of GPON-FTTH network for residential condominium, Conference on Computer Science and Software Engineering, (2017), 333-339. CrossRef M. BOUREGAA, M. CHIKH-BLED, Comparative Study of Optical Unipolar Codes for Incoherent DS-OCDMA system, International Journal of Hybrid Information Technology, 6 (2013) 225-236. CrossRef M. BOUREGAA, M. CHIKH-BLED, The performance of a DS-OCDMA system using Orthogonal Optical Codes (OOC), European Scientific Journal, 9 (2013), 322-335 CrossRef M. Iwase, Y. Ishikawa, T. Komatsu, J. Kasahara, N. Hattori, M. Miura, N. Nakamura, K. Odaka, Optical transceiver modules for gigabit Ethernet PON FTTH systems, Furukawa Review, 28 (2005) 8-10. DirectLink